Binder-Free Charantia-Like Metal-Oxide Core/Shell Nanotube Arrays for High-Performance Lithium-Ion Anodes - Xu, Pingping; Zhang, Ziying; Zhang, Huizhen; Shen, Ao; Zhao, Yangqiang; Zhou, Yangyang; Weng, Ying (Frontiers in Chemistry, 2020)
The performance of anodes of lithium-ion batteries relies largely on the architecture and composition of the hybrid active materials. We present a two-step, seed-free, solution-based method for the direct growth of hierarchical charantia-like TiO2/Fe2O3 core/shell nanotube arrays on carbon cloth substrates. An ultrahigh loading of the nanomaterial on carbon fibers was achieved with this method without the use of a binder. This three-dimensional porous hollow architecture and its direct contact with the CC current collector ensure an efficient electronic pathway. The hollow TiO2 framework effectively protects the hierarchical charantia-like TiO2/Fe2O3 hollow core/shell arrays from collapsing because of its negligible volume change during cycling. Meanwhile, the self-assembled α-Fe2O3 hollow nanospheres guarantee a large capacity and contact area with the electrolyte. This flexible anode with a 3D porous charantia-like hollow architecture exhibits high cycle performance, reversible capacity, and rate capability. These nanotube arrays maintain a high reversible capacity of 875 mAh g−1 after 200 cycles at a current density of 200 mA g−1. This simple, cost-effective, and scalable electrode fabrication strategy can be implemented in the fabrication of high-performance wearable energy storage devices.